2015
DOI: 10.14260/jemds/2015/1207
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Lipid Peroxidation and Antioxidants Enzymes in the Diagnosis and Prognosis of Gastrointestinal Carcinoma

Abstract: ABSTRACT:The present study mainly highlights the occurrence of lipid peroxidation and possible breakdown of antioxidants in gastrointestinal carcinoma patients as compared to healthy control subjects. Enzymatic and non-enzymatic parameters play an important role in cell protection against harmful influence of oxidative stress. Our aim of the present study was to investigate the levels of final lipid peroxidation products like (MDA) malondialdehyde and activity of antioxidative enzymes, superoxide dismutase (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The database search initially identified 574 publications through the database search, and ten studies were finally identified after meeting all inclusion criteria and requirements [ 13 – 22 ]. The ten published studies included 1,094 subjects, 495 patients with gastric cancer and 599 healthy individuals [ 13 – 22 ]. Table 1 shows the baseline characteristics of these subjects included in the ten studies, which were published from 1993–2015 [ 13 – 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The database search initially identified 574 publications through the database search, and ten studies were finally identified after meeting all inclusion criteria and requirements [ 13 – 22 ]. The ten published studies included 1,094 subjects, 495 patients with gastric cancer and 599 healthy individuals [ 13 – 22 ]. Table 1 shows the baseline characteristics of these subjects included in the ten studies, which were published from 1993–2015 [ 13 – 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ten published studies included 1,094 subjects, 495 patients with gastric cancer and 599 healthy individuals [ 13 – 22 ]. Table 1 shows the baseline characteristics of these subjects included in the ten studies, which were published from 1993–2015 [ 13 – 22 ]. Five controlled studies [ 13 , 15 , 16 , 20 , 22 ] included an equal number of patients with gastric cancer and normal subjects who were age-matched and sex-matched and who had not undergone any treatment before providing blood samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations